Validity and reliability of a Chinese version of the Bergen Work Addiction Scale - Liu, Yuanyuan; Tian, Hongjun; Chen, Xinying; Jia, Feng; Li, Ranli; Sun, Yun; Chen, Langlang; Zhu, Jingjing; Jiang, Deguo; Zhuo, Chuanjun (Frontiers in Psychology, 2023)
Background Work addiction (WA), which can impair personal relationships, engagement in recreational activities, and/or health, is a behavioral addiction. A tool for the early detection of WA in China is needed. Objective The aim of this study was to develop and determine the validity and reliability of a Chinese version of the Bergen Work Addiction Scale (C-BWAS). Methods Two hundred social workers who provided post-discharge services for adolescents with non-suicidal self-injury (NSSI) were enrolled in this study. The construct validity of the C-BWAS was assessed by confirmatory factor analysis (CFA). Criterion validity was assessed by conducting Pearson correlation analyses of C-CWAS scores with Hamilton Depression Scale (HAM-D) and Hamilton Anxiety Scale (HAM-A) scores. Cronbach’s α and the intra-class correlation coefficient (ICC) were used to evaluate the reliability of the C-BWAS. Results CFA confirmed a one-dimensional structure of the C-BWAS with good construct validity indices [comparative fit index (CFI) = 0.964, Tucker–Lewis index (TLI) = 0.951, root-mean-square error of approximation (RMSEA) = 0.079, and minimum discrepancy Ĉ/degrees of freedom (Cmin/DF) = 0.362]. The standardized regression weights ranged from 0.523 to 0.753. All C-BWAS items loaded on one major factor (loading weights, 0.646–0.943). Coefficients of correlation between C-BWAS scores and HAM-D and HAM-A scores were 0.889 and 0.933, respectively. The Cronbach’s α coefficient and ICC for the instrument was 0.837 and 0.905, respectively. Conclusion The presently developed C-BWAS showed very good reliability and acceptably validity. It can be employed as a useful tool for assessing WA severity in social workers who provide post-discharge services for adolescents with NSSI.